2000
DOI: 10.1029/2000jb900013
|View full text |Cite
|
Sign up to set email alerts
|

Seismovolcanic signals at Deception Island volcano, Antarctica: Wave field analysis and source modeling

Abstract: Abstract. The seismovolcanic signals associated with the volcanic activity of Deception Island (Antarctica), recorded during three Antarctic summers (1994-1995, 1995-1996 and 1996-1997), are analyzed using a dense small-aperture (500 m) seismic array. The visual and spectral classification of the seismic events shows the existence of long-period and hybrid isolated seismic events, and of low-frequency, quasi-monochromatic and spasmodic continuous tremors. All spectra have the highest amplitudes in the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…The study of the seismic activity of the volcano is probably the most active and productive research line, as reported by Tejedo et al (2014). There are many results that help us better understand the dynamic and volcanological framework of the area, such as Vila et al (1992), , Ibáñez et al (1997Ibáñez et al ( , 2000Ibáñez et al ( , 2003, Saccorotti et al (2001), Martinez-Arevalo et al (2003), Benitez et al (2007), Carmona et al (2010Carmona et al ( , 2012Carmona et al ( , 2014, and García-Yeguas et al (2010). One of the objectives of these seismic studies is to provide 2D or 3D structure of the area, by using active or passive data as has been done by Ben-Zvi et al (2009), Zandomeneghi et al (2009), and Prudencio et al (2013).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study of the seismic activity of the volcano is probably the most active and productive research line, as reported by Tejedo et al (2014). There are many results that help us better understand the dynamic and volcanological framework of the area, such as Vila et al (1992), , Ibáñez et al (1997Ibáñez et al ( , 2000Ibáñez et al ( , 2003, Saccorotti et al (2001), Martinez-Arevalo et al (2003), Benitez et al (2007), Carmona et al (2010Carmona et al ( , 2012Carmona et al ( , 2014, and García-Yeguas et al (2010). One of the objectives of these seismic studies is to provide 2D or 3D structure of the area, by using active or passive data as has been done by Ben-Zvi et al (2009), Zandomeneghi et al (2009), and Prudencio et al (2013).…”
Section: Introductionmentioning
confidence: 93%
“…1). Nowadays, its volcanic activity mainly consists of hot hydrothermal waters, fumarolic fields, and intense seismic activity composed by volcanic tremor, persistent long-period, and volcano-tectonic seismicity (Vila et al 1992;Ortiz et al 1997;Ibáñez et al 2000;Carmona et al 2012).…”
Section: Deception Island: Volcanological and Geophysical Modelsmentioning
confidence: 99%
“…In the framework of the Spanish Polar Program, the Andalusian Institute of Geophysics, University of Granada (IAG-UGR), has carried out research projects at Deception Island since 1994 to investigate the seismic activity and structure of the volcano and surrounding areas (e.g., Almendros et al, 1997Almendros et al, , 1999Benitez et al, 2007;Carmona et al, 2010Carmona et al, , 2012Carmona et al, , 2014García-Yeguas et al, 2011;Ibáñez et al, 1997Ibáñez et al, , 2000Ibáñez et al, , 2017Jiménez et al, 2017;Luzón et al, 2011;Prudencio et al, 2013Prudencio et al, , 2015Zandomeneghi et al, 2009). The IAG-UGR also monitors the seismic activity of Deception Island volcano and provides scientific advice for the management of the volcanic alert system.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods are used routinely to complement the time signal analyses in the seismic monitoring of volcanic areas in order to distinguish the different types of seismic events produced by volcanoes (e.g. Ibañez et al, 2000;Del Pezzo, 2003). Spectrograms are also useful as a complement in locating pyroclastic flows (Jolly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%